Analyzing IPO Underpricing Drivers: Evidence from Profitability, Market Value, and Leverage in Indonesia's Market - Ardiansyah, Faisal Aski; Jurana, Jurana; Muliati, Muliati; Masruddin, Masruddin (Economics, Business, Accounting & Society Review, 2025)
This study investigates the effect of profitability, financial leverage, and market value on stock underpricing in companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange from 2018 to 2022. Using a quantitative approach and multiple linear regression analysis, data were obtained from 189 companies selected through purposive sampling. The findings reveal that profitability, financial leverage, and market value simultaneously influence underpricing. Partially, profitability and market value have a significant negative effect on underpricing, while financial leverage shows no significant effect. The negative effect of profitability aligns with signaling theory, suggesting that high profitability signals low risk and strong performance, thus reducing the need for aggressive underpricing. Similarly, high market value indicates stronger investor perception and reduces uncertainty, leading to lower underpricing. Conversely, the insignificance of financial leverage implies that investors may not perceive debt levels as critical in IPO pricing, especially in regulated capital markets. This research contributes to the ongoing debate regarding the inconsistent effects of firm-specific financial indicators on underpricing across different contexts. The results highlight the contextual nature of IPO pricing decisions and suggest that market perception and external regulatory factors may moderate traditional financial indicators.